2010
DOI: 10.1007/s11420-009-9134-7
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious Effects of Intermittent Recombinant Parathyroid Hormone on Cartilage Formation in a Rabbit Microfracture Model: A Preliminary Study

Abstract: Intermittent parathyroid hormone administration can enhance fracture healing in an animal model. Despite the success of exogenous parathyroid hormone on fracture healing and spine fusion, few studies have examined the role of parathyroid hormone on cartilage formation. We determined the effects of intermittent parathyroid hormone on cartilage formation in a rabbit microfracture model of cartilage regeneration. Twelve rabbits were divided into three equal groups: (1) microfracture alone, (2) microfracture + par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The principal receptor-binding domain of PTHrP lies within amino acids (aa) 15-34, but the first 2 amino acids of PTH/PTHrP are essential for the activation of the cAMP/PKA-dependent pathway. The C-terminus of PTH/PTHrP , where PTH and PTHrP share structural rather than sequential homology, contains a domain necessary for PKC activation within aa [28][29][30][31][32][33][34]. N-terminally truncated peptide analogs such as PTHrP can bind to the receptor but do not elicit a cAMP/PKA response [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The principal receptor-binding domain of PTHrP lies within amino acids (aa) 15-34, but the first 2 amino acids of PTH/PTHrP are essential for the activation of the cAMP/PKA-dependent pathway. The C-terminus of PTH/PTHrP , where PTH and PTHrP share structural rather than sequential homology, contains a domain necessary for PKC activation within aa [28][29][30][31][32][33][34]. N-terminally truncated peptide analogs such as PTHrP can bind to the receptor but do not elicit a cAMP/PKA response [14].…”
mentioning
confidence: 99%
“…Few studies reported on an improved osteochondral repair [28,29], stimulation of chondrogenesis in bone healing during callus formation [30], and inhibition of osteoarthritis progression in an in vitro and in vivo azacytidine-induced osteoarthritis model [31]. In contrast, an inhibition of cartilage formation was observed in a microfracture study after intermittent treatment with PTH [32].…”
mentioning
confidence: 99%
“…That was the case of subcutaneously injected recombinant (1-34) PTH. 19 Notably, the findings of the study concerning the final outcome were opposite from the desired, as systemic administration of PTH led to induction of bone formation. On the other hand, the same findings indicate that systemic administration as a delivery method could prove rather effective.…”
Section: Discussionmentioning
confidence: 88%
“…Histologic and gross analysis showed that treatment with either 1 or 4 weeks of intermittent parathyroid hormone inhibited cartilage formation. 19…”
Section: Pharmaceutical Agentsmentioning
confidence: 99%
“…55 Feeley reported on the negative influence of postoperative parathyroid hormone treatment on cartilage formation in a rabbit microfracture model and recommended against its use. 56…”
Section: Bioactive (Growth) Factorsmentioning
confidence: 99%